Neurodinámica en el tratamiento fisioterapéutico del túnel del carpo - Alex Sebastián, Domínguez Bonilla (2021)
ABSTRACT The following research project states the Neurodynamic mobilization as a physiotherapeutic treatment in the carpal tunnel. Carpal tunnel syndrome is a condition where the middle nerve is trapped as it passes through the wrist. Carpal tunnel syndrome usually happens because tendons passing through the same place are in an inflammatory process. The middle nerve is in charge of the motor control which allows first finger movement by transporting information to the brain over the sensitive part of the fingers. When there is a median nerve trapping it can cause pain, tingling or numbness of the hand, these sensations may be even more critical at night with a significant disturbing of the sleep. Neurodynamics is a treatment that allows the mobilization and slippage of neural structures in the nervous system. Through movement and neural tension there will be an the improvement of the symptoms. This study consists of scientific material that was analyzed to demonstrate the effectiveness of Neurodynamics. To obtain results, 120 scientific articles were used to address the problem. A total of 35 articles were the basis for the development of the work. Out of this number, 22 scientific articles dealt with Neurodynamics in carpal tunnel syndrome, 13 on Neurodynamics and the different physiotherapeutic approaches. The articles analyzed in this study were obtained from the the following databases: Academica, Scielo, PubMed, Proquest, Elsevier, ResearchGate, Redalyc, Science direct, PEDro and the Google academic search engine. KEY WORDS: Syndrome, neurodynamics, tension, treatment, carpus, slippage, neural. Reviewed by: Mgs. Adriana Cundar Ruano Ph.D. ENGLISH PROFESSOR c.c. 1709268534